Economic background of dambadeniya, yapahuva, kurunegala, gampola and kotte that led to social changes - Wimalasena, N.A. (University of Jaffna, 2014)
The economic factor can be regarded as the decision of social development in a human society and with that development of the economic situation; various structures of a society similarly are described. Several scholars have analyzed through their various researches that commercial activities and development of commerce are major facts which a society will organize systematically in the world. The economic factor which was a reason for the origin and development of socio- political organization of ancient Sri Lanka can be studied under two major divisions. Those are an economy based on agricultural activities and economy based on trading activities. R. A. L. H. Gunawardhana has suggested that periods of prolific activity in building of irrigation works in Sri Lanka coincided with the most flourishing periods of trade. The explanation for this is that commercial gain provided the resources for hydraulic engineering. He points out that there was only one new major irrigation project undertaken between the seventh and the ninth centuries, in sharp contrast to the intense irrigation activity in the period immediately preceding. H. J. Benda has clearly shown from his primary studies that economy based on agriculture and commerce has affected the changes of society and political organization. Therefore, from this part, the growth of commercial activities will be discussed based on those views and how the commercial activities affected the society. Commerce is a factor which is based on buying of items, transaction, selling and consumption. A commercial market is a place where meeting of merchants and consumers takes place. When we study commercial history of ancient time, we need to note that there were two major parts which were called local trade and long distance trade. As has been pointed out by Classen, this idea had confirmed the origin of several society and states, and changes of societies as well. The social history of a country cannot be studied without knowledge of internal trade and international trade of that country because commercial activities affect very seriously to change a society. Those societies become very wealthy societies due to the commercial activities. In relation to Sri Lanka, it describes the growth of local trading activities and how far it affected the development of the Sri Lankan society. There seem to have been certain special economic forces and features that marked the changes that occurred in the medieval period. Therefore, major objective of this presentation is to discuss the economic factors that led to social changes during the period under review. The research will be mainly based on primary sources and wherever necessary material will also be obtained from limited secondary sources published on the political system of the island.
Keywords: Economy; Merchants; Human society; Commercial market; Internal and external trade